The basics of prospective public policy analysis (2017)
Given the inexistence in Spanish of an introductory synthesis to prospective policy analysis, this article proposes its conceptual and historical bases, the analysts' work and skills, and the ways to approach it, listing some of the most used methods and techniques . For this, the article reviews an important part of the English literature on the subject, organizing it descriptively for pedagogical and analytical purposes. Initially, the use of the expression public policy analysis is clarified, differentiating the field of public policy studies from the analysis applied within it to produce information for decision making; then the definition of policy analysis is discussed and an integrative definition is proposed. The second part deals with the historical aspects, the third glimpses the professional work of policy analysts, and the skills they require to carry it out (personal, political and technical). Finally, the article poses somes approaches for analysis and some useful techniques and methods to get started. The text ends by opening the discussion about policy analysis importance in the Latin American sphere to govern, as a field of knowledge that contributes to the strengthening of information management capacities, and to a more systematic process of decision making.